Implementation of Differentiated Learning Strategies in Writing Narrative Text for the Elevent Grade at SMAS Pertiwi Medan - Devi Maharani; Anggraini Thesisia Saragih (Universitas Negeri Medan, 2025)
This research examined the implementation of differentiated learning strategies in enhancing students' narrative writing skills at Class XI SMAS Pertiwi Medan. Using a qualitative approach with classroom observations and teacher interviews, the study investigated how differentiated learning affected students' writing development.The implementation focused on four key components: content adjustment through varied difficulty levels and materials, learning process variations using group discussions and peer tutoring, diverse product choices allowing students to create summaries, comics, videos, or drama performances, and creating a supportive learning environment. Students were grouped into three ability levels using fairy tales as learning materials. The findings revealed significant positive impacts: increased student motivation and engagement through autonomy and choice, improved narrative writing quality in structure and creativity, and enhanced student independence and confidence. However, implementation faced challenges including time limitations and resource constraints.The study concluded that differentiated learning effectively accommodated student diversity and significantly improved narrative writing skills while fostering independence and confidence, despite implementation challenges. Keywords: Implementation, Differentiated, Learning, Strategies, Narrative Text